PEMBENTUKAN KARAKTER GENERASI MILENIAL DALAM PERSFEKTIF SOSIOLOGI PENDIDIKAN - Poniam Poniam (CV. ADIBA AISHA AMIRA, 2024)
Advances in science and technology bring rapid changes both physically and psychologically. This has positive and negative impacts on every aspect of life, including the behavior or attitudes of society, including the millennial generation as the main users of technological advances. Changes in society's attitudes, namely the millennial generation, need careful attention and handling, especially changes that have a negative impact, one of which is abandoning the cultural character values of the nation and state. Implementation of education by developing character values that are considered to be lost include integrity, religiousness, mutual cooperation, nationalism and independence. The millennial generation is a generation that has an important role in the progress of the nation and state, therefore good character must be instilled in individuals. Sociology of Education in shaping the character of the millennial generation. Sociology as a science has a clear field of inquiry, point of view, methods and structure of knowledge. The object of research is human and group behavior. His point of view looks at the nature of society, culture and individuals scientifically. Meanwhile, the structure of knowledge consists of concepts and principles regarding the life of social groups, culture and personal development. With all the uniqueness that the sociology of education has, the study of the sociology of education emphasizes the social implications and consequences of education and views educational problems from the perspective of the totality of its socio-cultural, political and economic scope for society.